ANALISIS MUTU PELAYANAN PENYULUHAN PERTANIAN DAN KEPUASAN PETANI PADI SAWAH DALAM KEGIATAN PENYULUHAN PERTANIAN DI KELURAHAN BARUGA KECAMATAN BARUGA KOTA KENDARI - Ilham Saputra; Iskandar Zinuddin Rela; Tjandra Buana (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2024)
The quality of extension services is expected to generate satisfaction for farmers, which will then be useful in efforts to increase the capacity and quality of individual farmers. This study aims to assess the level of quality of extension services and farmer satisfaction in agricultural extension activities in Baruga Sub-district. The population of this study were all wet-rice farmers in Baruga Sub-district, which amounted to 287 people. The research sample was determined using the Slovin formula with an error rate of 10%, resulting in a sample size of 34 farmers. This research employed a quantitative approach. Data were collected through surveys, interviews, and document review, with the assistance of questionnaires. Quantitative descriptive analysis was used to process the data. The findings indicated that the quality of agricultural extension services in farming development activities in Baruga Village was generally rated as good or high. This can be observed in each indicator, namely tangible, reliability, responsiveness, assurance, and empathy, which have been executed optimally. Furthermore, the satisfaction of farmers with regard to agricultural extension activities in the development of farming in Baruga Village is evident. This is demonstrated by the positive response (satisfaction) of farmers to the actions of extension workers, which begins with the activities of extension service visits and extends to the satisfaction with the material presented, the ability to identify potential, and the satisfaction with the ability of extension workers to identify problems.